2020
DOI: 10.1213/ane.0000000000004959
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Ischemic Stroke–Specific Focus on Anesthetic Management for Mechanical Thrombectomy

Abstract: Acute ischemic stroke is a neurological emergency with a high likelihood of morbidity, mortality, and long-term disability. Modern stroke care involves multidisciplinary management by neurologists, radiologists, neurosurgeons, and anesthesiologists. Current American Heart Association/American Stroke Association (AHA/ASA) guidelines recommend thrombolytic therapy with intravenous (IV) alteplase within the first 3–4.5 hours of initial stroke symptoms and endovascular mechanical thrombectomy within the first 16–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Based on the anesthesia types, it was confirmed that the use of general anesthesia caused a considerable delay. Recent studies have not been able to prove the superiority or inferiority of one anesthesia type over the other [ 1 ]. One may prefer general anesthesia, given the advantages of patient’s airway maintenance and ease of irritability control and the potential risks of conversion from local anesthesia to general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the anesthesia types, it was confirmed that the use of general anesthesia caused a considerable delay. Recent studies have not been able to prove the superiority or inferiority of one anesthesia type over the other [ 1 ]. One may prefer general anesthesia, given the advantages of patient’s airway maintenance and ease of irritability control and the potential risks of conversion from local anesthesia to general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…GA is also recommended for patients who are vomiting or unable to cooperate. If MAC is the chosen technique, the procedural anesthesiologist should be ready to convert to GA if the patient experiences deteriorating neurological status, seizures, or procedural complications 28 . There is no evidence to support the use of any one agent over another through the use of shorter-acting agents may facilitate earlier neurological assessment after the procedure 26 …”
Section: Intraprocedural Considerationsmentioning
confidence: 99%
“…There may be a role for depth of anaesthesia monitoring. It has been noted that doses of anaesthetic drugs used for both general anaesthesia and sedation during thrombectomy were uncharacteristically low compared with typical doses used in different circumstances [34]. As there is limited access to the patient, long extensions are recommended for infusions and fluid lines.…”
Section: Anaesthetic Managementmentioning
confidence: 99%